Consumer perceptions on privacy and confidentiality in dermatology for 3D total‐body imaging. (8th November 2022) - Horsham, Caitlin; Janda, Monika; Kerr, Melissa; Soyer, H. Peter; Caffery, Liam J.
Abstract: As 3D total‐body photography for the early detection of melanoma is not yet widely used in clinical practice, we do not have a full understanding of patient's concerns about use, privacy and confidentiality, and if their concerns differ depending on the use‐case. We conducted a virtual consumer forum to assess patients concerns about privacy and confidentiality in dermatology imaging for research, artificial intelligence development and for their own clinical care.